kepuasan pasien Hubungan Tingkat Pelayanan Kesehatan Terhadap Kepuasan Pasien Dengan BPJS Di Rs An-nisa Tangerang - Fitra Abdul Malik Fitra (Jurnal Riset Media Keperawatan, 2026)
Health is a basic human need to be able to live decently and productively. Optimal public health is a reflection of maximum health services. Health services are one of the fundamental rights of the community whose provision must be carried out by the government as mandated in the 1945 Constitution. The purpose of this study is to examine the relationship between the level of health services and patient satisfaction with BPJS at An-Nisa Hospital, Tangerang. This research method uses a quantitative method with a cross-sectional design with Spearman Rank analysis. The results of this study are: In 394 patient respondents who said they were very satisfied with the health services provided were 260 (66%) respondents, and those who said they were less satisfied with the health services provided were 43 (10.9%). Based on the results of the Spearman rank statistical test obtained a significant number or probability number (0.001) below the significant value of 0.05 or (p <a), then Ho is rejected and Ha is accepted which means there is a relationship between the level of health services and patient satisfaction with BPJS at An-Nisa Hospital, Tangerang.